Agaricobiota do Pampa e da Mata Atlântica: diversidade e comestibilidad - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The use of wild mushrooms as food in Brazil still comes up against the lack of identification guides and biodiversity surveys associated with different biomes. The Pampa Biome, for example, has been very little explored so far in terms of taxonomic surveys, let alone culinary ones. In order to evaluate the biodiversity of edible mushrooms in two different biomes in Rio Grande do Sul, Pampa and Atlantic Forest, the present work was proposed. The survey was carried out using the walking methodology and the collection of specimens was carried out according to the usual methods for macromycetes. Native and exotic essence forests were visited in both biomes and literature data from the areas were evaluated. Quarterly collections for one year were performed and data compared. Identification guides for representatives of the two families with the highest number of species used for food, Agaricaceae and Strophariaceae, were assembled based on literature review and prepared as review articles. 165 species of mushroons of the Agaricaceae family were confirmed for Brazil, 41 edible and 12 toxic. A total of 137 species of Strophariaceae have been cited and confirmed in Brazil, of which 21 are edible and 43 are poisonous and/or hallucinogenic. In the surveys of native forests, 8 new occurrences were confirmed for the Pampa Biome, as follows Blumenavia rhacodes Möller, Macrolepiota mastoidea (Fr. Ex Fr.) Singer, Protostropharia alcis ssp. austrobrasiliensis (Cortez & R.M. Silveira) C. Hahn, Trogia buccinalis (Mont.) Pat., Crepidotus euterpicola Senn-Irlet & De Meijer, Entoloma depluens (Batsch) Hesler, Lepiota subincarnata J.E. Lange, Neopaxillus echinospermus (Speg.) Singer. Comparing data from the Atlantic Forest Biome with regard to edible species, it was found that these species alone connot meet the daily needs of nutrients for a human being, however, when used as complementary to regular food, these can be an excelente nutritional source.
Keywords: Cogumelos; Comestibilidade; Sustentabilidade; Mushrooms; Edibility; Sustainability; CNPQ::CIENCIAS BIOLOGICAS